Exploring the Impact of Post-Pandemic Learning Strategies on University Students’ Engagement and Academic Achievement - Jihan Jihan; Samuel Mamonto; Endang Fatmawati; Ika Suhartanti Darmo; Muas Muchtar (AL-ISHLAH: Jurnal Pendidikan, 2023)
In the context of campus-based education, this study aims to investigate how post-pandemic learning strategies affect students' levels of engagement with their coursework as well as their overall academic performance. In this study, a quantitative approach is taken, and the participants are students in an English language education study program in the city of Palu who take a campus-based learning approach to their education. The type of research is correlational and non-experimental.  Google Forms and other similar online survey distribution and gathering platforms facilitate this process. The results showed that the adoption of post-pandemic learning strategies that were inclusive and adaptive had a positive impact on student engagement, and post-pandemic learning strategies that were inclusive and adaptive had a positive impact on their academic achievement. In addition, post-pandemic learning strategies also indirectly affect student academic achievement through student involvement. This research provides recommendations for the development of post-pandemic learning strategies that are more inclusive and adaptive in campus-based education to increase student engagement and academic achievement.